Reduced miR‐513a‐5p expression in COPD may regulate airway mucous cell hyperplasia through TFR1‐dependent signaling - Jia Zhou; Jun‐Yi Du; Rui Xu; Xiao‐Juan Wu; Guo‐Yue Zhang (Kaohsiung Journal of Medical Sciences, 2024)
Abstract Airway mucous cell metaplasia and mucous hypersecretion is one of the key characteristic pathophysiological status of chronic obstructive pulmonary disease (COPD). micro(mi)RNAs are acknowledged as non‐encoding RNA molecules playing important roles in gene expression regulation. In this study, we searched the Gene Expression Omnibus (GEO) database for the differentially expressed miRNAs between COPD and non‐COPD controls with bioinformatics analysis. Finally, we focused on miR‐513a‐5p and investigated the potential mechanism by which miR‐513a‐5p regulates airway mucous hypersecretion and goblet cell metaplasia. A dual‐luciferase reporter assay was then showing that miR‐513a‐5p targeted the 3′‐UTR of TFR1 and inhibited its expression in vitro. In vivo transfection demonstrated that TFR1 downregulation partially blocked MUC5AC hypersecretion and goblet cell hyperplasia in COPD model rats. In vitro study, CSE increased the intracellular expression and secretion of MUC5AC by BEAS‐2B branchial epithelial cells in the BEAS‐2B cell and THP‐1 cell coculture system. Coculture with either miR‐513a‐5p mimic‐pretreated or TFR1‐deficient THP‐1 cells attenuated intracellular MUC5AC expression in BEAS‐2B cells exposed to CSE. ELISA demonstrated that transfection of TFR1 siRNA or pretreatment with miR‐513a‐5p mimic reduced the secretion of inflammatory factors that are responsible for airway goblet cell hyperplasia, such as IL‐1β, IL‐13, and IL‐17, by THP‐1 cells after CSE stimulation. Our findings supported that miR‐513a‐5p/TFR1 signaling axis might activate macrophages as well as promote airway inflammation and airway mucous cell hyperplasia in COPD.